2020
DOI: 10.1155/2020/7520736
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Use of Hylocereus polyrhizus Peels as a Source of Cosmeceutical Sunscreen Agent for Its Antioxidant and Photoprotective Properties

Abstract: Currently, consumers’ demand for sunscreens derived from natural sources that provide photoprotection from ultraviolet (UV) radiation is pushing the cosmetic industry to develop breakthrough formulations of sun protection products by incorporating plant antioxidants as their active ingredients. In this context, the present study was initiated to evaluate the antioxidant and photoprotective properties of the underutilized Hylocereus polyrhizus peel extract (HPPE) using in vitro spectrophotometric techniques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
0
14
0
3
Order By: Relevance
“…The results of a study performed by Vijayakumar et al [ 114 ] demonstrated that H. polyrhizus bark extract is a potent antioxidant with photoprotective properties. In addition, the phenolic compounds and flavonoids helped the overall antioxidant properties, the high sun protection factor value, and broad-spectrum UVA and UVB photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study performed by Vijayakumar et al [ 114 ] demonstrated that H. polyrhizus bark extract is a potent antioxidant with photoprotective properties. In addition, the phenolic compounds and flavonoids helped the overall antioxidant properties, the high sun protection factor value, and broad-spectrum UVA and UVB photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…All of them exhibit SPF values above 6 when used alone in O/W emulsion at 10% (wt.%), and above 16.5 and PF-UVA above 7.5 when used in combination [129]. Hylocereus polyrhizus at 1 mg/mL demonstrated an SPF of about 35 [130]. Pterodon emarginatus extract at 10% (w/w) in three different formulations (Lanette ® , Polawax ® and Focus Gel ® ) exhibited an SPF value of about 8 [131].…”
Section: The Effect Of Plant Secondary Metabolite Treatment On Kerati...mentioning
confidence: 98%
“…To get rid of oxidative stress, fruits have applied ROS scavenging strategy. SOD and CAT play essential roles in this defense [4,71]. Besides, LOX regulates fruit development at different stages, which is tightly associated with the generation and identification of stress signals [51].…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Red pitahayas (Hylocereus polyrhizus), originating from Latin America and the West Indies [1], have attracted much attention worldwide due to attractive appearance, high nutritional value, and various biological activities [2][3][4]. However, the fruits are highly perishable, mainly caused by fungal diseases, degreening, and physiological disorders [5,6], which shortens its postharvest shelf life during distribution and marketing.…”
Section: Introductionmentioning
confidence: 99%